Prostate cancer detection using quantitative T2 and T2‐weighted imaging: The effects of 5‐alpha‐reductase inhibitors in men on active surveillance. Issue 6 (14th November 2017) - Giganti, Francesco; Gambarota, Giulio; Moore, Caroline M.; Robertson, Nicola L.; McCartan, Neil; Jameson, Charles; Bott, Simon R.J.; Winkler, Mathias; Whitcher, Brandon; Castro‐Santamaria, Ramiro; Emberton, Mark; Allen, Clare; et al.
Abstract : Background: T2 ‐weighted imaging (T2 ‐WI) information has been used in a qualitative manner in the assessment of prostate cancer. Quantitative derivatives (T2 relaxation time) can be generated from T2 ‐WI. These outputs may be useful in helping to discriminate clinically significant prostate cancer from background signal. Purpose/Hypothesis: To investigate changes in quantitative T2 parameters in lesions and noncancerous tissue of men on active surveillance for prostate cancer taking dutasteride 0.5 mg or placebo daily for 6 months. Study Type: Retrospective. Population/Subjects: Forty men randomized to 6 months of daily dutasteride ( n = 20) or placebo ( n = 20). Field Strength/Sequence: Multiparametric 3T MRI at baseline and 6 months. This included a multiecho MR sequence for quantification of the T2 relaxation times, in three regions of interest (index lesion, noncancerous peripheral [PZ] and transitional [TZ] zones). A synthetic signal contrast (T2 Q contrast) between lesion and noncancerous tissue was assessed using quantitative T2 values. Signal contrast was calculated using the T2 ‐weighted sequence (T2 W contrast). Assessment: Two radiologists reviewed the scans in consensus according to Prostate Imaging Reporting and Data System (PI‐RADS v. 2) guidelines. Statistical Tests: Wilcoxon and Mann–Whitney U ‐tests, Spearman's correlation. Results: When compared to noncancerous tissue, shorter T2 values were observed within lesions at baseline (83.5 and 80.5 msec) and 6 months (81.5 and 81.9 msec) in the placebo and dutasteride arm, respectively. No significant differences for T2 W contrast at baseline and after 6 months were observed, both in the placebo (0.40 [0.29–0.49] vs. 0.43 [0.25–0.49]; P = 0.881) and dutasteride arm (0.35 [0.24–0.47] vs. 0.37 [0.22–0.44]; P = 0.668). There was a significant, positive correlation between the T2 Q contrast and the T2 W contrast values ( r = 0.786; P < 0.001). Data Conclusion: The exposure to antiandrogen therapy did not significantly influence the T2 contrast or the T2 relaxation values in men on active surveillance for prostate cancer. Level of Evidence: 4 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1646–1653.